PENGARUH INKUIRI DAN PJBL BERSUMBER POTENSI LOKAL TERHADAP PEMAHAMAN KONSEP, KETERAMPILAN PROSES SAINS, DAN SIKAP ILMIAH SISWA - Faridah, Listia Adhayul; Sari, Murni Sapta; Ibrohim, Ibrohim (Universitas Negeri Malang, 2017)
Biology learning in the 2013 curriculum emphasizes the development of holistic attitude, knowledge, and skills competencies. One way to develop these competencies is by applying a learning model based on a scientific approach, namely inquiry and PjBL. Both of these models have stages that can develop the three competencies. The purpose of this research is to know the influence of inquiry learning model and PjBL toward concept comprehension, scientific process skill, and scientific attitude. The type of this research is experiment using nonrandomized pretest and posstes control group design. The instrument of this research is the observation sheet of scientific attitude and scientific process skill, and concept comprehension test. Analysis of scientific attitude data using anova, data analysis of scientific process skills using kruskal wallis, and analysis of concept comprehension data using anacova. The result of analysis of anakova test obtained F count equal to 65,494 with significance level p (0,000) <α (0,05), Anova test result got χ2 count equal to 44,325 with significance level p (0,000) <α (0,05), test result Anova obtained F count equal to 26,795 with significance level p (0,000) <α (0,05). The three test results show that there are differences in scientific attitude, scientific process skills, and conceptual understanding between control class students and experimental class students.